ADDRESSING THE PROFICIENCY OF VOCATIONAL TEACHERS IN INCORPORATING DIGITAL TOOLS IN CLASSROOM: THE CURRENT AND CHALLENGES - Ni Luh Silvia Pernanda Putri (UHN IGB Sugriwa Denpasar, 2025)
The advancement of digital technology is transforming educational practices worldwide. One instructional model reflecting this shift is Bloom’s Digital Taxonomy (BDT), which refer to Bloom’s cognitive framework through the integration of digital tools and tasks. Despite its potential, many vocational high school English teachers encounter challenges in applying BDT effectively due to varied digital proficiency and institutional limitations. The drawbacks of its implementation become the main issue which needs to be further investigated. This study aimed to see the proficiency level of Vocational High School English teachers in integrating technology into instructions based on BDT as well as the factors influencing Vocational School English teachers’ proficiency in integrating technology into instructions based on BDT framework. In order to obtain the result, the present study conducted an explanatory sequential mixed-methods design. This design was selected as it presents a comprehensive analysis of the methods in which quantitative results were extended and explained by the qualitative results. The data were collected from 20 English teachers across seven vocational schools through questionnaires and semi-structured interviews. The findings revealed that that most teachers more proficient at the “Applying” level (C3) of BDT, reflecting ability to use digital tools in instructional practices. Influencing factors included school facilities, curriculum requirements, digital training opportunities, teaching experience, and teacher collaboration. The study recommends future research to explore the integration of BDT and the TPACK framework using longitudinal methods, particularly within non-formal education contexts.